Stent-Save a Life international survey on the practice of primary coronary angioplasty during the COVID-19 pandemic. (14th October 2021) - Pereira, H; On Behalf Of Stent Save A Life Initative, S S L
Abstract: Aims: To evaluate the impact of the COVID-19 pandemic on patient admissions with acute coronary syndromes (ACS) and primary coronary angioplasty (PPCI) in countries participating in the Stent-Save a Life (SSL) global initiative. Methods and results: We conducted a multicenter, observational survey to collect data on patient admissions for ACS, STEMI and PPCI in the SSL participating countries throughout a period during the COVID-19 outbreak (March and April 2020) compared with the equivalent period in 2019. From the 32 member countries of the SSL global initiative, 17 accepted to participate in the survey (3 from Africa, 5 from Asia, 6 from Europe and 3 from Latin America (LATAM)). We observed a global reduction of 27, 5% and 20, 0% in admissions with ACS and STEMI respectively. The decrease in PPCI was 26, 7% (Figure 1). This trend was observed in all countries except two. In these two countries, the pandemic peaked later than in the other countries. Conclusions: This survey shows that the COVID-19 outbreak was associated with a significant reduction of hospital admissions for ACS and STEMI as well as a reduction of PPCI, which can be explained by both patient and system related factors. Funding Acknowledgement: Type of funding sources: None.